Serbs in the Danube Region (XVIII – early XX centuries) - Liliya Tsyganenko (Journal of Danubian Studies and Research, 2015)
The territory of the Ukrainian Danube region – unique in terms of the ethnic region in the historical development of which contributed to the representatives of various ethnic groups and peoples: Ukrainians, Russians, Moldovans, Bulgarians, Germans, Armenians and others. They were among the settlers on the banks of the Danube and a few representatives of the Serbian people. The article discusses the history of the emergence of Serbian immigrants in the region; their settlement on lands Izmail districts in the XVIII – early XX centuries; the participation in economic, political, religious, cultural, educational and administrative life of the region.